7.(x - 1) = 2.(3x + 1)
Soluções para a tarefa
Respondido por
19
7.(x - 1) = 2.(3x + 1) 1° passo - fazer a distributiva
7 . x - 7 . 1 = 2 . 3x + 2 . 1
7x - 7 = 6x + 2 2° passo - isolar o x
7x - 6x = 2 + 7
x = 9
______________________________________*
Demasiado, respostas corretas em demasia
______________________________________*
7 . x - 7 . 1 = 2 . 3x + 2 . 1
7x - 7 = 6x + 2 2° passo - isolar o x
7x - 6x = 2 + 7
x = 9
______________________________________*
Demasiado, respostas corretas em demasia
______________________________________*
Respondido por
15
7.(x - 1) = 2.(3x + 1)
7x - 7 = 6x + 2
7x - 6x = 2+7
x = 9
________*
Gannicus
________*
7x - 7 = 6x + 2
7x - 6x = 2+7
x = 9
________*
Gannicus
________*
Perguntas interessantes
Inglês,
1 ano atrás
Português,
1 ano atrás
Português,
1 ano atrás
Pedagogia,
1 ano atrás
Matemática,
1 ano atrás
Sociologia,
1 ano atrás